2021
DOI: 10.1002/esp.5172
|View full text |Cite
|
Sign up to set email alerts
|

Lateral bedrock erosion and valley formation in a heterogeneously layered landscape, Northeast Kansas

Abstract: In this study, we present direct field measurements of modern lateral and vertical bedrock erosion during a 2-year study period, and optically stimulated luminescence (OSL) ages of fluvial material capping a flat bedrock surface at Kings Creek located in northeast Kansas, USA. These data provide insight into rates and mechanisms of bedrock erosion and valley-widening in a heterogeneously layered limestone-shale landscape. Lateral bedrock erosion outpaced vertical incision during our 2-year study period. Modern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 78 publications
0
10
0
Order By: Relevance
“…River valleys evolve by deepening through vertical river incision and widening through lateral erosion of valley walls (Figure 1). Whereas much emphasis has been put on investigating processes and rates of vertical incision (e.g., Tucker & Slingerland, 1997; Tucker & Whipple, 2002), our limited knowledge on parameters controlling valley widening and valley‐bottom width prevents us from interpreting the range of valley geometries that occur in nature and predicting how valleys evolve under changing environmental conditions (Langston & Tucker, 2018; Marcotte et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…River valleys evolve by deepening through vertical river incision and widening through lateral erosion of valley walls (Figure 1). Whereas much emphasis has been put on investigating processes and rates of vertical incision (e.g., Tucker & Slingerland, 1997; Tucker & Whipple, 2002), our limited knowledge on parameters controlling valley widening and valley‐bottom width prevents us from interpreting the range of valley geometries that occur in nature and predicting how valleys evolve under changing environmental conditions (Langston & Tucker, 2018; Marcotte et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…in nature and predicting how valleys evolve under changing environmental conditions (Langston & Tucker, 2018;Marcotte et al, 2021).…”
mentioning
confidence: 99%
“…Lateral migration of channels may be an important control on both channel profiles (Finnegan and Dietrich, 2011) and the evolution of drainage networks over geological timescales (Kwang et al, 2021). Some studies have suggested that lateral erosion rates can outpace those of vertical incision (Suzuki, 1982;Cook et al, 2014;Marcotte et al, 2021), yet research into rates and mechanisms of lateral erosion is distinctly lacking compared to vertical bedrock incision.…”
Section: Introductionmentioning
confidence: 99%
“…Valley and channel width further plays a central role in landscape evolution (Amos and Burbank, 2007;Fisher et al, 2013;Hancock and Anderson, 2002). The relation between valley width, which subsumes channels, terraces, and floodplains, and other measures of valley morphology, including depth and fill thickness, is used to elucidate drainage evolution over geological timescales (e.g., Gibling, 2006;Schumm and Ethridge, 1994) and for inferring past climate changes (e.g., Dury, 1964;Hancock and Anderson, 2002;Marcotte et al, 2021) and tectonic variations (Giaconia et al, 2012). The channel width is a key component in landscape evolution for its control on the shear stress exerted by the flowing water, sediment transport capacity, and erosion rate (Whittaker et al, 2007b;Yanites et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, in such landscapes, a more complex scaling involving channel width, area, and slope was shown to be more applicable (Finnegan et al, 2005). While the influence of tectonic, climatic, and lithologic changes on valley and channel width has been extensively explored (e.g., Allen et al, 2013;Keen-Zebert et al, 2017;Marcotte et al, 2021), the effects of drainage reorganization, which imposes drainage area transiency, were mostly overlooked. The current study targets these effects by exploring valley and channel width scaling under transient conditions that emerge from processes of drainage reorganization.…”
Section: Introductionmentioning
confidence: 99%